Determination of future designers’ professionally important coordination qualities - S. M. Chernovsky; A. N. Kolumbet (Physical Education of Students)
Purpose: to find out girl students’ motor abilities, influencing to the largest extent on successfulness of designer’s professional functioning. Material: 210 girl students of 18-22 years’ age participated in experiment. Results: it was found that all indicators of future designers’ professional qualities are closely connected with indicators of definite coordination abilities. High interconnection with kinesthetic indicators and girl students’ professional skillfulness were noted. It was determined that quickness, concentration and re-switching of attention were closely connected with attention, operative memory, accuracy of reproduction of received information. Conclusions: for girl students-designers’ successful professional progress it is necessary to develop kinesthetic, responding and orientation coordination qualities. These qualities are required for quick and effective solution of professional tasks, connected with accurate perception in the shortest possible time and keeping great volume of space information in memory.